Innovative Vocabulary Learning Through Games-Based Learning at SMKN 3 Parepare - Nurul Faradillah; Isumarni Isumarni; Nurhikmah Nurhikmah; Yadinda Mahardika Darwis Putri; Septita Puteri Namirta; Sam Hermansyah; Nanda Putri; Winda Aprilia (Universitas Muhammadiyah Enrekang, 2024)
Vocabulary is a fundamental aspect of language proficiency, serving as a critical foundation for communication, comprehension, and academic success. However, many vocational high school students face challenges in mastering English vocabulary due to teaching methods that often overlook individual differences in learning needs and abilities. This study explores the implementation of the